“Implementación de una central telefónica voz IP utilizando software libre Issabel PBX y comunicaciones unificadas basado en Asterisk en la constructora MA Construcciones”. - Defaz Parra, Kevin Andrés (2020)
This project consists of implementing a telephone exchange using the Issabel tool to allow communication between the different departments and the reduction of telephone costs for the “MA Construcciones” company. It is a private institution oriented to provide consulting services for civil, hydraulic, architecture and construction engineering that it is located in the province of Tungurahua in the city of Ambato in the Izamba parish. This research is directed towards the customization of the design of a telecommunications platform; making use of Voice IP technologies and its benefits such as cost reduction with the use of free software Issabel and Asterisk, which allow the functionalities of a Call Center and VoIP, it covers the communication needs with users. It is determined as a solution for the “MA Construcciones”. It improves internal communication between the different departments of the company and the reduction of costs in telephone sheets due to the improper use of the traditional telephone. Finally, the budget used in the implementation is specified in order to provide a better service.